2022
DOI: 10.3390/agriculture12050625
|View full text |Cite
|
Sign up to set email alerts
|

Does Political Participation Influence the Waste Classification Behavior of Rural Residents? Empirical Evidence from Rural China

Abstract: Waste classification is an important part of the renovation of rural human settlements, and the renovation of rural human settlements is also of great significance to global sustainable development. Therefore, it is of the utmost importance to study the factors that affect the classification behavior for promoting waste classification behavior. However, few studies have focused on the political participation of rural residents as a driving factor. Therefore, this study aims to explore whether political partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…The mandatory promotion of waste classification contributes to increasing the recycling rate of resources, reducing the risk of supplying critical raw materials [58], and reducing the human and material costs required for back-end waste disposal [59,60]. According to the results of the analysis of influencing factors, we found that individual characteristics, family status, difficulty perception, governance attitude, environmental emotions, community attributes, operating rules, perception of the current situation, external action situation, and expected outcomes have an impact on the farmers' classification behavior, which is more consistent with the findings of existing studies [61][62][63]. The core factors affecting the waste farmers' classification behavior are mainly regional disparity, demonstration village, Party affiliation, operating rules, and emotional support perception; i.e., the key to activating the endogenous motivation of farmers to participate in waste classification from the root is based on the construction of a system that is reasonable, scientific, standardized, and meets the needs of farmers and respects their opinions.…”
Section: Discussionsupporting
confidence: 86%
“…The mandatory promotion of waste classification contributes to increasing the recycling rate of resources, reducing the risk of supplying critical raw materials [58], and reducing the human and material costs required for back-end waste disposal [59,60]. According to the results of the analysis of influencing factors, we found that individual characteristics, family status, difficulty perception, governance attitude, environmental emotions, community attributes, operating rules, perception of the current situation, external action situation, and expected outcomes have an impact on the farmers' classification behavior, which is more consistent with the findings of existing studies [61][62][63]. The core factors affecting the waste farmers' classification behavior are mainly regional disparity, demonstration village, Party affiliation, operating rules, and emotional support perception; i.e., the key to activating the endogenous motivation of farmers to participate in waste classification from the root is based on the construction of a system that is reasonable, scientific, standardized, and meets the needs of farmers and respects their opinions.…”
Section: Discussionsupporting
confidence: 86%
“…Prior research has demonstrated that WSB can be successfully encouraged by legislative restrictions [ 21 , 22 ]. Rural residents have stronger perceived economic losses and will be more willing to restrain their behavior to avoid unnecessary economic losses [ 24 ]. In urban areas, many residents have formed daily habits of waste separation and do not need to rely on too many external restraints.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, some waste sorting professional service companies joined in, such as “love classification”, where recyclable items are rewarded with 0.8 yuan per kilogram of “environmental protection gold”. Some scholars believe that groups receiving government subsidies may be more likely to understand the government's waste separation policy, and thus carry out waste separation [ 24 ]. However, some studies have shown that economic incentives are ineffective, and direct material incentives even discourage residents' sorting behavior [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, initiatives based on policy or political perspectives have not been considered. However, knowing the environmental policy process and its relationship to a country's waste management is crucial [13]. In contrast to past research, this study seeks to analyze the effectiveness of local government political communication with civil society power.…”
Section: Introductionmentioning
confidence: 99%